Synthesis, structures and magnetism of three AE-Dy(III)-CPs. (1st July 2022) - Hou, Jieqiong; Chen, Yanmei; Zhu, Lihong; Zou, Shuixiang; Dong, Wenwen
Graphical abstract: Three new AE-Dy (Ln = Ca(II), Sr(II), Ba(II)) coordination polymers with different 2D layer structures were synthesized. Complex 1 is a 4, 5-connected 2D layer network with a topology symbol of 3·4 3 ·5 2 3 2 ·4 4 ·5 2 ·6 2 . There is a [AEO]n chain in complexes 2 and 3 . They all have good thermal stability and exhibit antiferromagnetic interactions between the Dy(III) ions. Abstract: Three new coordination polymers, [Dy2 (pda)4 (Hnda)2 Ca2 (H2 O)2 ]·MeOH (1 ) (H2 nda = 2, 3-naphthalenedicarboxylic acid; H2 pda = 2, 6-pyridinedicarboxylic acid), [Dy(pda)2 (nda)AE2 (HCOO)(H2 O)] (AE = Sr (2 ), Ba (3 )), have been solvothermal synthesized and characterized. All of the polymers exhibit 2D framework structures, but with different topologies. Complex 1 is a 4, 5-connected 2D layer network with a topology symbol of 3·4 3 ·5 2 3 2 ·4 4 ·5 2 ·6 2 . There is a [AEO]n chain in complexes 2 and 3 . The coordination polymers have good thermal stability and they all maintain their skeleton structures below 430 °C. Magnetic property studies indicate that antiferromagnetic Dy(III)···Dy(III) interactions occur for 1 –3 . Ac susceptibility measurements reveal that the complexes exhibit single-molecule magnetic (SMM) behaviour.